C3 deficiency promotes pulmonary inflammation in AT1R-induced mouse model for systemic sclerosis - Yin, Junping; Verschoor, Admar; Yue, Xiaoyang; Goldmann, Torsten; Heidecke, Harald; Riemekasten, Gabriela; Petersen, Frank; Yu, Xinhua (Frontiers in Immunology, 2024)
IntroductionAutoantibody-mediated complement activation plays an essential role in a variety of autoimmune disorders. However, the role of complement in systemic sclerosis (SSc) remains largely unknown. In this study, we aimed to determine the role of complement C3 in the development of a recently described SSc mouse model based on autoimmunity to angiotensin II receptor type 1 (AT1R).MethodsMice were immunized with cell membrane extract isolated from Chinese hamster ovary (CHO) cells overexpressing AT1R or non-transfected CHO cells as a control. Peripheral blood, dorsal skin and the lung were then collected to evlauate disease characteristics. Apoptotic cells in the lung of mice were detected using the DeadEnd™ Fluorometric TUNEL System.ResultsOur results showed that experimental SSc in this model was featured by the deposition of IgG, but not of complement C3, in the lung. After immunization with AT1R, C3-deficient mice developed more severe pulmonary inflammations than wild type controls, whereas skin inflammation and fibrosis were not different as well as the anti-AT1R ab levels. Further, C3-deficient mice showed an increased rate of pulmonary cell apoptosis as compared to controls. The apoptosis rate correlated with the corresponding degree of lung inflammation.DiscussionTaken together, our findings suggest an anti-apoptotic and anti-inflammatory role of complement C3 in pulmonary autoimmune inflammation.